Faktor-Faktor yang Berhubungan dengan Peran Keluarga dalam Menunjang Kesembuhan Pasien dengan Kasus Tuberculosis - Irwan Budiana; Yoseph Woge; Yustina Pacifia Maria Paschalia (Journal of Telenursing (JOTING), 2021)
This study aims to determine the relationship between age, gender, education, occupation, marital status and belief in the role of the family in supporting the recovery of patients with TB cases. This research method uses a quantitative design with a correlational analytic approach. The technique of determining the respondents used the probability simple random sampling method. The results showed that the chi-square test results for the age variable were 0.332, 0.450 for gender, 0.021 for education, 0.686 for work, 0.717 for marital status and 0.002 for belief. As for the role of the family in supporting the recovery of patients with TB cases, the majority of respondents were categorized as moderate, namely 22 people (64.7%). In conclusion, the variables of age, gender, education, occupation and marital status did not have a significant relationship with the role of the family in supporting the recovery of patients with TB cases. Meanwhile, the belief variable has a significant relationship with the role of the family in supporting the recovery of patients with TB cases. Keywords: Family, Healing, Role, Pulmonary Tuberculosis